PENGEMBANGAN MODUL PENGANTAR STATISTIK DESKRIPTIF PADA MATA KULIAH STATISTIK DASAR UNTUK MAHASISWA PENDIDIKANFISIKA UNIVERSITAS MATARAM - Satutik Rahayu; Ahmad Harjono; Sutrio Sutrio; I Wayan Gunada; Hikmawati Hikmawati (Universitas Pendidikan Mandalika, 2014)
This study aims to produce a module product 'introduction of descriptive statistics' on the basic statistics course for physics education students’ academic year 2013/2014. This research uses 4-D model which consists of four stages: 1. Define, 2. Design, 3. Develop, and 4. Disseminate. The subjects are students studying basic statistics courses in the third semester. Data analysis using descriptive analysis and percentage. The results showed that the student response to the module was 71.5% (strongly agree), and 28.5% (agree). Therefore, we conclude that the modules that have been developed are ready for dissemination